Pharmacokinetic and pharmacodynamic characterisation of JNJ-40411813, a positive allosteric modulator of mGluR2, in two randomised, double-blind phase-I studies. (April 2015) - Salih, Hiba; Anghelescu, Ion; Kezic, Iva; Sinha, Vikash; Hoeben, Eef; Van Nueten, Luc; De Smedt, Heidi; De Boer, Peter
Metabotropic glutamate receptor-2 positive allosteric modulator, JNJ-40411813 (ADX71149), was characterised for clinical effects in healthy volunteers in two phase-1 studies. In study 1, healthy men received 50-, 100-, 150- or 225 mg and women received 100 mg JNJ-40411813 ( n =6, each cohort) or placebo ( n =2, each cohort) twice daily for seven days; smoking men ( n =30) received placebo twice daily on days 1−7, 100 mg JNJ-40411813 ( n =20) or placebo ( n =10) on days 8−14. In study 2, healthy men received intravenous 0.005 mg/kg S(+) ketamine over 60 min at 3 ( n =24; cohort 1), 12 h ( n =8; cohort 3), and 24 h ( n =8; cohort 2) after a single oral dose of 500 mg JNJ-40411813 or placebo. The pharmacokinetics and effects of JNJ-40411813 on cognition and subjective awareness were evaluated. Plasma JNJ-40411813 exposure was dose-dependent, t max ranged from 3−4 h and t 1/2 19.4−34.2 h across the dose levels. JNJ-40411813 significantly ( p =0.02) reduced continuity of attention score (150 mg dose) and ameliorated smoking withdrawal-induced changes in power of attention and quality of episodic memory versus placebo. A modest reduction in alertness was observed at 150–225 mg doses, JNJ-40411813 (500 mg) reduced S(+) ketamine-induced negative symptoms by approximately 43% and 30% in cohorts 1 and 3, respectively. JNJ-40411813 was generally well-tolerated.